2008
DOI: 10.1007/s15010-007-6354-y
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Herpesvirus DNA in Cerebrospinal Fluid and Correlation with Clinical Symptoms

Abstract: The detection of low-level herpesvirus replication in CSF by highly sensitive PCR assays requires critical evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 9 publications
(13 reference statements)
0
19
0
Order By: Relevance
“…In miscellanous neurological patients CNS "colonization" with EBV seems to be rare [6,7]. However, in infectious mononucleosis the CSF is often positive for EBV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In miscellanous neurological patients CNS "colonization" with EBV seems to be rare [6,7]. However, in infectious mononucleosis the CSF is often positive for EBV.…”
Section: Discussionmentioning
confidence: 99%
“…In 208 patients with various neurological diseases, among whom the clinician did not request any herpesvirus PCR, no CSF sample was found positive for EBV [6]. Among 253 encephalitis patients studied in France in 2007, only 2,3% had EBV as etiology [7].…”
Section: Introductionmentioning
confidence: 99%
“…[99][100][101][102] Although HSV-1 preferentially lies dormant in neurons, the detection of HSV-1 DNA in the cerebrospinal fluid suggests that asymptomatic replication of HSV-1 may occur in the CNS under certain cirucumstances. 103,104 Given the intense interplay between HSV-1 and host cells, it is likely that recurrent HSV-1 reactivation may cumulatively arouse neuronal dysfunction, as demonstrated recently by Martin et al, 105 which shows that HSV-1 reactivation from latency induces neuroinflammation and the appearance of early neurodegenerative markers including MAPT/Tau phosphorylation. In line with this, independent analyses of large cohorts of subjects revealed a significantly increased risk for AD in patients with anti-HSV-1 IgM, a marker of viral primary infection or reactivation.…”
Section: Hsv-1-associated Autophagy Dysfunction: a Risk Factor For Nementioning
confidence: 93%
“…There is no clear evidence on whether HSV-1 reaching the brain and infecting neurons resides there in latent form. However, the detection of HSV-1 DNA in the cerebro-spinal fluid (Deatly et al, 1988; Peter and Sevall, 2001; Plentz et al, 2008) suggests that HSV-1 replicates in the CNS (Bearer, 2012). The presence of HSV-1 proteins in hippocampal neurons of mice infected intraperitoneally with HSV-1 was demonstrated by Burgos et al (2006a) who also showed that virus is reactivated by hyperthermia.…”
Section: How Can Hsv-1 Be Involved In Ad?mentioning
confidence: 99%